2021
DOI: 10.3390/polym13071077
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Laminates of Commercially Available Fabrics for Anti-Stab Body-Armor

Abstract: Modern personal protective armor has been generally based on the Kevlar fabrics, with the main goal to offer defense against bullets. In addition to the high cost and poor processability, Kevlar has the disadvantage of limited stab-proofing capability. On the other hand, a large number of crimes involving deadly injures represent knife attacks. Our goal in this work was to investigate composites based on traditional commercially available fabrics of linen and silk, using different adhesives-polymers for formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Khuyen et al avoided technical fibers and investigated the stab-resistance of composites with linen and silk plain weave fabrics in water-based PU, urea formaldehyde (UF) and poly(vinyl alcohol) (PVA) matrices [ 63 ]. The highest tensile strength was found for linen/UF; manual (and thus highly subjective) stabbing tests were performed with an undefined blade, where 20 layers of hard silk/UF, resulting in a thickness of 7.9 mm, showed sufficient results.…”
Section: Reinforced Polymers and Composites For Stab Resistancementioning
confidence: 99%
“…Khuyen et al avoided technical fibers and investigated the stab-resistance of composites with linen and silk plain weave fabrics in water-based PU, urea formaldehyde (UF) and poly(vinyl alcohol) (PVA) matrices [ 63 ]. The highest tensile strength was found for linen/UF; manual (and thus highly subjective) stabbing tests were performed with an undefined blade, where 20 layers of hard silk/UF, resulting in a thickness of 7.9 mm, showed sufficient results.…”
Section: Reinforced Polymers and Composites For Stab Resistancementioning
confidence: 99%
“…15 Many scholars also considered the potential application of TPU in stab-resistant material. 16 Khuyen et al 17 used three different adhesives, polyurethane (PU), urea formaldehyde (UF) and poly(vinyl alcohol) (PVA), to form fabric laminates. The results indicate that the presence of all three adhesives can have a positive effect on the tensile strength, hardness, and bonding strength of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also been reported on vests with fluids that change their viscosity under impact, consuming a substantial part of the impact energy [14,[21][22][23]. However, these solutions cannot currently be mass-produced, and researchers' interest is equally focused on high-performance fibres, usually organised in fabrics [24][25][26][27][28]. For stab protection, polymeric fibres are used [29], as well as carbon fibres [30] and metallic fibres [31], sometimes in bold combinations [32], with natural [33] but…”
Section: Introductionmentioning
confidence: 99%